Purdon's Digest. A Digest of the Laws of Pennsylvania, from the Year One Thousand Seven Hundred to the Twenty-Eighth Day of May, One Thousand Eight Hundred and Fifty-three, at 150, Concealed Weapons, § 1 (1853) - (:unkn) unknown (My University, 1853)
Any person within the limits of the city and county of Philadelphia, who shall carry any fire-arms, slung-shot or other deadly weapon concealed upon his person, with the intent therewith unlawfully and maliciously to do injury to any other person, shall be deemed guilty of a misdemeanor, and upon the conviction thereof, shall be sentenced to undergo solitary confinement at hard labor in the prison of said county for a period of not less than one month, nor more than one year, at the discretion of the court; and the jury trying the case may infer such intent as aforesaid, from the fact of the said defendant carrying such weapons in the manner as aforesaid
Keywords: CARRY - CONCEALED